ANALYSIS OF NURSING AUDIT IMPLEMENTATION ON QUALITY OF CARE SUBCOMMITTEE IN A HOSPITAL AT JAKARTA - MARINA TARIGAN; Enie Novieastari; Sri Purwaningsih (Alta Dharma Publisher, 2019)
A nursing audit is a professional evaluation of the quality of nursing services provided for patients by employing medical records or other supporting data conducted by nursing staff. This research aimed to investigate the root causes of the nursing audit performed by the quality care subcommittee in the hospital. To gain the data, the researchers employed secondary methods consisting of observation and interview. The collected data were analyzed by employing a systematic methodology to investigate the root causes by employing the Ishikawa diagram. The analysis results are presented by employing the 5-M method. The solution is proposed as a feedback to the hospital to develop a nursing audit. Meanwhile, the recommendation is rendered to the hospital to improve the quality of nursing care of the hospital particularly the nursing committee in performing nursing audits conducted by the quality care subcommittee by developing a documentation audit system. Keywords: Nursing audit, Ishikawa diagram, quality care subcommittee